Sulfur and Carbon Co‐doped TiO2 Composite Fabricated by Lignosulphonate and Its Suitability for Removal of Cadmium. Issue 9 (17th September 2019) - Zou, Xiao‐Hang; Shang, Xu‐Ting; Wang, Rui‐Jia; Zhang, Ji‐Guo; Pan, Qing‐Jiang; Guo, Yuan‐Ru
Abstract: Highly toxic divalent cadmium causes serious environmental issues. To quickly monitor and/or efficiently remove this potentially toxic metal ion as well as to explore its interfacial chemistry with metal oxides, a sulfur and carbon co‐doped titania (S/C‐TiO2 ) composite is synthesized via a facile sol‐gel method with the assistance of sodium lignosulphonate (SLS). The prepared composite displays a well‐crystallized TiO2 nanostructure comprising the anatase phase. Both S and C, which are derived from the SLS template, are found to enter the TiO2 lattice. The S/C‐TiO2 composite exhibits a porous structure with a wide pore size distribution. The newly synthesized composite shows adsorption capability for the potentially toxic metal Cd(II). The adsorption process requires <5 min to reach equilibrium. The measured equilibrium adsorption capacity is 19.42 mg g −1, which is twice as high as that of bare TiO2 . The removal efficiency is as high as 97%. Moreover, the materials are suitable for contaminated solutions over a wide range of pH values and various initial cadmium concentrations. A mechanism for the enhanced adsorption behavior is also proposed. Abstract : Sulfur and carbon codoped titania has been synthesized by a facile sol‐gel method with sodium lignosulphonate. The newly prepared composite shows good adsorption capability for Cd(II) in a very fast process.